A rare cause of childhood chylothorax: Gorham-Stout disease: Gorham-Stout disease in children - Mocan Cağlar, Yasemin; Can Oksay, Sinem; Toksöz Yıldırım, Ayşe Nur; Bozbeyoğlu, Sabriye Gülçin; Girit, Saniye (Journal of Surgery and Medicine, 2025)
Gorham syndrome is an extremely rare bone disease, with only a limited number of cases reported worldwide. It is characterized by progressive bone resorption associated with abnormal proliferation of lymphatic vessels, making it a rare case in medical literature. This disorder can lead to serious complications including chylothorax, especially in children. Early diagnosis and treatment are crucial in the prevention of life-threatening outcomes. This report presents a case of a young child with recurrent pleural effusion and bone lesions, eventually diagnosed with Gorham’s disease. A three-year-old patient was admitted with recurrent pleural effusion, chylothorax, and pneumothorax. Imaging revealed multiple lytic bone lesions, suggestive of bone destruction. A lung biopsy confirmed lymphatic dilation, supporting a diagnosis of Gorham’s disease. The patient’s condition was evaluated through a multidisciplinary approach involving pulmonology, pathology, and radiology teams. Treatment included a combination of pharmacotherapy and dietary modifications, which successfully stabilized the patient’s condition. The child has since been closely monitored, with no significant recurrence of symptoms. The progression of the disease can be life-threatening, particularly when the thoracic duct is involved, leading to recurrent pleural effusions. In this particular case, early diagnosis through a collaborative medical approach allowed for prompt treatment. Ongoing monitoring is essential in preventing relapses and ensuring long-term health outcomes for the patient.